Penguatan Landasan Epistemologi dalam Pengembangan Kurikulum Pendidikan Agama Islam dan Budi Pekerti Sekolah Dasar untuk Meningkatkan Karakter Siswa - Ishak, Encep (Perkumpulan Peneliti dan Pegiat Literasi, 2024)
This study focuses on the importance of the epistemological foundation in the development of Islamic Religious Education (PAI) curriculum in PAI and Character Education subjects at the elementary school level. As a basis for shaping the understanding and practice of Islamic religion, the epistemological foundation plays a crucial role in developing a relevant and meaningful curriculum. The purpose of this research is to analyze how the epistemological foundation influences the development of the PAI curriculum and its implications in the context of Islamic religious education. Using a qualitative approach with library research methods, data were obtained from various relevant primary and secondary sources. The findings show that the epistemological foundation significantly contributes to creating more effective religious education, which in turn impacts the formation of Muslim students' character and religious commitment. The study also reveals that the integration of epistemology in the development of the PAI curriculum not only strengthens the relevance of religious education but also prepares students to face modern social and technological challenges. The limitations of this study lie in the scope of the literature reviewed, and further studies with broader coverage are suggested to explore the practical implementation of these findings in the field.